Impact of exercise training and sleep on children’s stress perception - Pagani, Eleonora; Oggionni, Gianluigi; Giovanelli, Luca; Mariani, Anna; Bernardelli, Giuseppina; Lucini, Daniela (Frontiers in Sports and Active Living, 2025)
BackgroundA healthy lifestyle is currently considered a pillar in the prevention/treatment of chronic non-communicable diseases in both adulthood and childhood. Notably, it is also a prominent tool for fostering wellbeing and managing stress, particularly at a young age when these two lifestyle components play a fundamental role in determining present and future health.PurposeThis study aimed to evaluate the link between stress perception and lifestyle habits, particularly exercise and sleep in children/adolescents and their parents, using a simple anonymous questionnaireMethodsMembers of 50 families filled out a simple ad hoc anonymous questionnaire on lifestyle habits (exercise, sleep, nutrition, etc.) and stress/health/performance perceptions. The questionnaire was based on standardized instruments (International Physical Activity Questionnaire and the American Heart Association Healthy Diet Score), including objective indicators such as exercise volume and self-developed ordinal evaluation scales ranging from 0 to 10 that assessed subjective perceptions (e.g., health, stress, and performance). Anthropometric, systolic and diastolic arterial pressures, and heart rate data were also collected.ResultsIn children/adolescents, stress perception negatively correlated with the volume of moderate–vigorous exercise and time dedicated to sleep. The latter also correlated positively with the perception of health and academic performance and negatively with perception of fatigue, somatic symptoms, and systolic arterial pressure percentiles. When considering data from all the family members, we also observed interesting significant correlations between parents' exercise habits, parents' perceptions of health, and parents' perceptions of somatic symptoms and the perception of stress reported by their children, respectively.ConclusionIn this observational study, exercise and good sleep hygiene represent important tools to counteract stress perception in youth, fostering present and future wellbeing and health. The collection of lifestyle data using a simple questionnaire with simple clinical parameters may offer an opportunity to construct an immediate picture of family members' lifestyles, which may motivate parents and institutions to focus on improvement of lifestyle components (in particular, exercise and good sleep) instead of only focusing on traditional risk factors (such as dyslipidaemia, obesity, hypertension, and smoking) to foster present wellbeing in children/adolescents and prevent chronic non-communicable diseases.